2020
DOI: 10.1097/pcr.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous Carcinoma of the Prostate: A Unique Presentation of a Rare Entity and Review of the Literature

Abstract: Adenosquamous carcinoma of the prostate is an exceedingly rare and aggressive histologic variant of prostate cancer, which is composed of glandular and squamous components. Up to two-thirds of these cases are identified in patients with a history of adenocarcinoma after treatment with androgen deprivation therapy or radiation therapy; however, multiple cases have been reported arising de novo. Patients frequently present with obstructive urinary complaints and bony osteolytic metastases. Serum prostate-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These tumors can also have normal serum PSA and PAP. Risk factors for the development of prostatic adenosquamous carcinoma can include prior radiation and/or hormonal therapy [6], none of which our patient had received. There have been several documented cases of pASC in the absence of hormonal or radiotherapy, and some authors have suggested that this may reflect pluripotent cells capable of multidirectional differentiation [7].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These tumors can also have normal serum PSA and PAP. Risk factors for the development of prostatic adenosquamous carcinoma can include prior radiation and/or hormonal therapy [6], none of which our patient had received. There have been several documented cases of pASC in the absence of hormonal or radiotherapy, and some authors have suggested that this may reflect pluripotent cells capable of multidirectional differentiation [7].…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, these forms of prostate cancer carry a poor prognosis with a median survival estimated at 12-14 months [6]. The disease is also frequently metastatic at diagnosis most commonly spreading to bones and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%